Médiation familiale : quelle place pour les violences conjugales ? - Casas Vila, Glòria (Empan, 2009)
Cet article vise à rendre compte des enjeux sexués sous-jacents à la mise en place de la coparentalité en France, notamment à partir du développement du dispositif de la médiation familiale, en relation avec la problématique des violences masculines dans le cadre de la famille. En effet, un ensemble de dispositifs légaux récemment promulgués redéfinissent les rapports entre les parents (notamment les pères) et les enfants après une séparation ou un divorce. Au-delà des rapports de filiation, ces réformes juridiques pèsent également sur les rapports entre ex-conjoints : des rapports traversés par les inégalités de genre et marqués, dans certains cas, par l’emprise et la violence que les hommes exercent sur les femmes.
Keywords: cours; cycles supérieurs; discipline; droit; europe; fem7000; france; médiation; régions géographiques; science politique et droit; thématiques; violences; violences conjugales

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires